2013
DOI: 10.1074/jbc.m112.414516
|View full text |Cite
|
Sign up to set email alerts
|

Thiolactomycin-based β-Ketoacyl-AcpM Synthase A (KasA) Inhibitors

Abstract: Background: Potent inhibitors of the tuberculosis drug target KasA are needed. Results: Three-position analogs of the natural product thiolactomycin (TLM) were designed based on transient one-dimensional NOEs that reveal the relative orientation of TLM and a pantetheine analog bound simultaneously to KasA. Conclusion: Three-position analogs of TLM bind to KasA with increased potency. Significance: Optimization of TLM will lead to improved inhibitors of KasA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
(32 reference statements)
0
23
0
Order By: Relevance
“…Validated chemotypes may now be rapidly advanced using target-based optimization including structure based drug design which takes advantage of the rapidly increasing numbers of M. tb crystal structures available. These structures also open the door to other discovery techniques which are showing great promise including fragment-based drug design techniques as has already been applied to the discovery of novel antigen 85C inhibitors [76]. Fragment-based drug design has many advantages over traditional HTS approaches, including a much better coverage of chemical space which is compressed at lower molecular weights, considerably increasing the random statistical chance of finding true binders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Validated chemotypes may now be rapidly advanced using target-based optimization including structure based drug design which takes advantage of the rapidly increasing numbers of M. tb crystal structures available. These structures also open the door to other discovery techniques which are showing great promise including fragment-based drug design techniques as has already been applied to the discovery of novel antigen 85C inhibitors [76]. Fragment-based drug design has many advantages over traditional HTS approaches, including a much better coverage of chemical space which is compressed at lower molecular weights, considerably increasing the random statistical chance of finding true binders.…”
Section: Discussionmentioning
confidence: 99%
“…Substitutions included alkyl, branched alkyl, unsaturated alkyl and aromatic groups and they found that the isoprenyl group was required for activity [74]. To help further the SAR, Kapilashrami et al modified the alkyl group at the 3-position [76]. Substitutions included alkyl, acyl and aromatic functional groups [76].…”
Section: New Inhibitors Of the Mycolic Acid Biosynthetic Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…The 2D spectra often produced weak ILOE cross-peaks with interference from F1 apodization noise due to intense methyl resonance from metformin and some of the other ligands at the high concentrations (~5 mM) used in these studies. Improved signal-to-noise and artifact free spectra were obtained using 1D ILOE experiments 55 obtained using an Agilent 800 MHz NMR spectrometer equipped with a cryogenic triple resonance probe. The 1D ILOE experiments were carried out using the ChemPack (Agilent Inc, Santa Clara CA) NOESY1D experiment.…”
Section: Methodsmentioning
confidence: 99%